2008
DOI: 10.1016/j.drugalcdep.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a closing gender gap in alcohol use, abuse, and dependence in the United States population

Abstract: BACKGROUND-Descriptively, male-female differences in alcohol consumption and alcohol use disorders appear to have decreased in birth cohorts reaching adulthood since the 1970s compared to earlier birth cohorts. However, such birth cohort effects on gender differences have never been statistically tested in nationally representative data. The aim of this study was to test the hypothesis that gender differences in alcohol consumption, abuse, and dependence are decreasing over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
320
3
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 453 publications
(370 citation statements)
references
References 59 publications
38
320
3
9
Order By: Relevance
“…Gender convergence in alcohol use is leading to a narrowing of differences in mental disorders, such as major depression and substance disorders. 8,20 Older people, on the other hand, had the greatest gender difference in our study, corroborating literature findings. 34,35 As discussed above, social rules and roles have changed in recent years.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Gender convergence in alcohol use is leading to a narrowing of differences in mental disorders, such as major depression and substance disorders. 8,20 Older people, on the other hand, had the greatest gender difference in our study, corroborating literature findings. 34,35 As discussed above, social rules and roles have changed in recent years.…”
Section: Discussionsupporting
confidence: 82%
“…1,21 Second, the expressive female entry into the workforce, increasing female opportunities regarding birth control and other indicators of gender role equality may be important factors contributing to a narrowing of gender differences. 4,8,21,22 In our study, men were likely to drink larger quantities of alcoholic beverages and more frequently than women. We have also found that men had higher prevalence rates of frequent binge drinking, namely heavy drinking, which is in agreement with the evidence from other studies conducted in Brazil 13,23 and other countries in Latin America, such as Mexico and Costa Rica.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…There is some evidence that the sex gap in drinking prevalence is getting smaller (Center for Disease Control, 2013; Keyes et al, 2008) and that the heritability of alcoholism does not differ by sex (Prescott & Kendler, 2000). Moreover, a recent study found that childhood maltreatment and other life stressors were predictive of later stress-related drinking among women (Young-Wolff, Kendler, & Prescott, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this study tests whether gender moderates stress reactivity at the level of both mood reactivity (i.e., positive mood, negative mood, and anxiety) and stress-induced craving for alcohol. This may be especially important given recent evidence that the sex gap in alcohol use may be closing ("Vital signs: Binge," 2013; Keyes, Grant, & Hasin, 2008). Based on the aforementioned studies, it is hypothesized that men will report greater stress-induced alcohol craving than women, and that women will show greater negative emotional response to stress induction than men.…”
Section: Introductionmentioning
confidence: 99%